Rhytomus Génier & Saxton: A new dung beetle genus from New Guinea with five new species and phylogenetic insights (Coleoptera: Scarabaeidae: Scarabaeinae) - Génier, François; Gunter, Nicole L.; Saxton, Natalie A. (Zootaxa, 2025)
In this study, we utilize both morphological and molecular data of Australasian dung beetles to establish Rhytomus Génier & Saxton, new genus. Using ultra-conserved element (UCE) data, we reconstruct the relationships between Rhytomus and related genera within the Australasian endemic clade. We provide a comprehensive revision for all mainland New Guinea species including the description of five new species: R. fervidus Saxton & Génier, new species, R. larseni Saxton & Génier, new species, R. latidentatus Saxton & Génier, new species, R. sodalis Saxton & Génier, new species, and R. vanus Saxton & Génier, new species. We transfer seven species originally described within the genus Tesserodon Hope, 1837; Rhytomus heurni (Paulian, 1937), new combination, Rhytomus howdeni (Paulian, 1985), new combination, Rhytomus papuanus (Paulian, 1985), new combination, Rhytomus seramicus (Krikken & Huijbregts, 2009), new combination, Rhytomus setulosus (Balthasar, 1965), new combination, Rhytomus waigeoensis (Ochi, Kon & Hartini, 2017), new combination. Furthermore, we designate a lectotype for Tesserodon elongatum van Lansberge, 1885, correct name bearing type data for Tesserodon howdeni Paulian, 1985 and provide both a traditional dichotomous and an online illustrated interactive identification key for mainland New Guinea species.